Drug development for cystic fibrosis. (12th January 2021) - Sanders, Don B.; Chmiel, James F.
Abstract: The first regulatory approval for a drug developed specifically for cystic fibrosis (CF) occurred in 1993, and since then, several other drugs have been approved. Median predicted survival in people with CF in the United States has increased from approximately 30 years to 44.4 years over that same period. Highly effective modulators of the cystic fibrosis transmembrane conductance regulator became available to approximately 90% of people with CF ages 12 years and older in the United States in 2019 and in Europe in 2020. These transformative therapies will surely reduce morbidity and further extend longevity. The drug development pipeline is filled with therapies that address most aspects of CF disease. As survival and CF therapies advance, and the complexity of CF care increases, the process of drug development has become more sophisticated. In addition, detecting meaningful changes in outcome measures has become more difficult as the health status of people with CF improves. Innovative approaches are required to continue to advance drug development in CF. This review provides a general overview of drug development from the preclinical phase through Phase IV. Special considerations with respect to CF are integrated into the discussion of each phase of drug development. As CF care evolves, drug development must continue to evolve as well, until a one‐time cure is available to all people with CF.